Onboard energy storage in rail transport: Review of real applications and techno‐economic assessments - Emanuele Fedele; Diego Iannuzzi; Andrea Del Pizzo (IET Electrical Systems in Transportation)
Abstract Despite low energy and fuel consumption levels in the rail sector, further improvements are being pursued by manufacturers and operators. Their primary efforts aim to reduce traction energy demand, replace diesel, and limit the impact of electrified overhead infrastructures. From a system‐level perspective, the integration of alternative energy sources on board rail vehicles has become a popular solution among rolling stock manufacturers. Surveys are made of many recent realizations of multimodal rail vehicles with onboard electrochemical batteries, supercapacitors, and hydrogen fuel cell systems. The ratings, technical features, and operating data of onboard sources are gathered for each application, and a comparison among different technologies is presented. Traction system architectures and energy‐control strategies of actual multimodal units are explored and compared with literature research. Moreover, the maturity and potential of recent technologies and alternative topologies of power converters for multimodal traction systems are discussed. Ultimately, onboard storage systems are compared with other solutions for energy‐saving and catenary‐free operation, with particular focus on their current techno‐economic attractiveness as an alternative to diesel propulsion.